Implementasi Mata Kuliah Jurnalistik pada Magang Pembelajaran Berbasis Proyek pada Harian Bhirawa - Hariyanti, Ayunda; Hanifah, Mutiara Mujahidah; Sundari, Ismi Putri; Hafidloh, Nurul; Istiqomah, Istiqomah (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity describes the implementation of a journalism course through a Project Based Learning (PBL) internship program at Harian Bhirawa as a service partner. The program provides mentoring and practical learning that enables students to apply journalistic competencies directly in a professional media environment. The method involves training and supervised fieldwork practice. Results indicate that the PBL-based internship improves students’ abilities to apply 5W+1H, the inverted pyramid structure, and journalistic ethics in news reporting. Students also show improved skills in interviewing, field observation, data processing, news writing, and video editing according to Harian Bhirawa’s editorial standards. The program offers authentic learning experiences that strengthen journalistic competencies while fostering soft skills such as critical thinking, effective communication, teamwork, and adaptability. Therefore, this internship program serves as an effective model for bridging academic learning with the needs of the media industry.